An Efficient Synthesis of (±)-Cycloillicinone - Wateh, Amy Nuzwir; Thy, Chun Keng; Chee, Chin Fei; Abd Rahman, Noorsaadah (Taylor & Francis, 2015)
An efficient synthesis of (±)-cycloillicinone was accomplished in five steps from sesamol. The title compound was obtained via a biomimetic Diels-Alder cycloaddition between illicinone A and β-trans-ocimene as the key step.